Dynamics of double emulsion break-up in three phase glass capillary microfluidic devices - Nabavi, Seyed Ali; Gu, Sai; Vladisavljević, G. T.; Ekanem, E. E. (Elsevier, 2015)
Pinch-off of a compound jet in 3D glass capillary microfluidic device, which combines co-flowing and countercurrent flow focusing geometries, was investigated using an incompressible three-phase axisymmetric Volume of Fluid–Continuum Surface Force (VOF–CSF) numerical model. The model showed good agreement with the experimental drop generation and was capable of predicting formation of core/shell droplets in dripping, narrowing jetting and widening jetting regimes. In dripping and widening jetting regimes, the presence of a vortex flow around the upstream end of the necking thread facilitates the jet break-up. No vortex flow was observed in narrowing jetting regime and pinch-off occurred due to higher velocity at the downstream end of the coaxial thread compared to that at the upstream end. In all regimes, the inner jet ruptured before the outer jet, preventing a leakage of the inner drop into the outer fluid. The necking region moves at the maximum speed in the narrowing jetting regime, due to the highest level of shear at the outer surface of the thread. However, in widening jetting regime, the neck travels the longest distance downstream before it breaks.
Keywords: Drop microfluidics; Dripping regime; Narrowing jetting; Widening jetting; Core-shell droplets; Flow focusing; Vortex flow; Pinch-off mechanism; VOF–CSF model; Glass capillary device